Stereoselective total synthesis and structural revision of the diacetylenic diol natural products strongylodiols H and I - Gangadhar, Pamarthi; Ramakrishna, Sayini; Venkateswarlu, Ponneri; Srihari, Pabbaraja (Beilstein Journal of Organic Chemistry, 2018)
The stereoselective total synthesis of strongylodiol H and I has been accomplished. The synthetic procedure comprised the stereoselective reduction of a ketone functionality in an ene–yne–one employing CBS as a catalyst and a Cadiot–Chodkiewicz coupling reaction as the key reaction steps. A common aldehyde intermediate has been used for the synthesis of both strongylodiols.
Keywords: alkylation; Cadiot–Chodkiewicz coupling; Corey–Bakshi–Shibata reduction; Mosher’s analysis; Wittig reaction